Safeguarding MTC at the Physical Layer: Potentials and Challenges - Osorio, Diana Pamela Moya; Olivo, Edgar Eduardo Benitez [UNESP]; Alves, Hirley; Latva-Aho, Matti (Institute of Electrical and Electronics Engineers (IEEE), 2020)
5G networks must provide a highly resilient, secure, and privacy-protected platform to support the emergence of new business and technologies expected from the so-called vertical-industry paradigm. However, as the definition and implementation of 5G networks are in progress, many security challenges arise. Thus, special emphasis will be given in the coming years to provide security and privacy for 5G and beyond networks. In this regard, physical layer security has been recognized as a potential solution to safeguard the confidentiality and privacy of communications in such stringent scenarios. In light of this, herein we provide an overview on some promising physical-layer techniques, focusing on the requirements and design challenges for machine-type communication scenarios. Key issues are discussed along with potential solutions.
Keywords: 5G and beyond networks; Critical and massive Machine-Type Communications (mMTCs); Internet of Things (IoT); Physical layer security